ЗАРУБІЖНИЙ ДОСВІД ОРГАНІЗАЦІЇ ДІЯЛЬНОСТІ ІНСТИТУТУ ДІЛЬНИЧНИХ ОФІЦЕРІВ ПОЛІЦІЇ (КОМПАРАТИВІСТСЬКЕ ДОСЛІДЖЕННЯ) - Головков, Олександр Миколайович (SUPREMANCE OF LAW, 2017)
The article is devoted to the analysis of the organization the institute’s activity of the police precinct offi cers in foreign countries and to determination the opportunity of establishing their positive experience in the Ukrainian police system. The author explores the experience of police activity in such countries as the United States of America, Australia, Japan, China, Italy, Germany, Hungary, Poland, Latvia, Lithuania, Estonia, Azerbaijan, Belarus, Armenia, Kazakhstan, Kyrgyzstan, Moldova, Russian Federation, Tajikistan, Turkmenistan, Uzbekistan. The author proves that the modern administrative activities of police precinct officers are gradually approaching the concept of democratic policing in the leading countries of the world.